One Billion Hungry Can We Feed the World? - Conway, Gordon (Cornell University Press, 2012)
Hunger is a daily reality for a billion people. More than six decades after the technological discoveries that led to the Green Revolution aimed at ending world hunger, regular food shortages, malnutrition, and poverty still plague vast swaths of the world. And with increasing food prices, climate change, resource inequality, and an ever-increasing global population, the future holds further challenges.In One Billion Hungry, Sir Gordon Conway, one of the world's foremost experts on global food needs, explains the many interrelated issues critical to our global food supply from the science of agricultural advances to the politics of food security. He expands the discussion begun in his influential The Doubly Green Revolution: Food for All in the Twenty-First Century, emphasizing the essential combination of increased food production, environmental stability, and poverty reduction necessary to end endemic hunger on our planet.